The use of identified parameter limits in a robust adaptive controller - Beaven, R.W.; Wright, M.T.; Friswell, M.I. (Control engineering practice, 1997)
This paper describes a self-tuning regulator (STR) developed from simplified H∞ controller synthesis and recursive least squares with variable forgetting-factor parameter-estimation algorithms, for single axes of high-speed servo drive systems. The problem of controller modifier and system identifier interaction causing numerical instability in the STR algorithm, leading to system instability, is examined. A method of overcoming this problem by the use of identified parameter limits is given. The STR results, for a simulated system, are compared to an H∞ controller and a PID with velocity feedforward controller.